A novel design methodology on cascaded fractional order (FO) PI-PD control and its real time implementation to Cart-Inverted Pendulum System. (November 2022) - Mondal, Reetam; Dey, Jayati
Abstract: The tune up of fractional order (FO)- P I λ D μ controllers is largely advocated in available literature which mostly requires evolutionary optimization techniques or solution of complex non-linear equations thereby leading to lack of practical solutions in terms of selecting the controller parameters. It may be quite feasible if one can consider PID control in the form of cascaded P I − P D control with which the task of attainment of the control objectives can be accomplished methodically. In extension to this, studies related to FO P I λ − P D μ controller are not too exhaustive. Generally, graphical methods are adopted to compute the controller parameters. There is still paucity of comprehensive design algorithms for these controllers to which end this work comes up with a novel and simple specification driven design methodology of the cascaded structures of FO P I λ − P D μ and [ P I ] λ − [ P D ] μ controllers following the classical control theory Keeping away from the complex and implicit design strategies they assist with an exact and unique solution to design these FO controllers in frequency domain with satisfactory dynamic performance in time domain which may not be possible with the FO- P I λ D μ controllers. Illustrative examples and experimental validations aid to substantiate the reliability of the proposed method. Highlights: A novel specification driven design methodology of two distinct cascaded structures of fractional order (FO) PI-PD controllers. Exact and unique solution to design these FO controllers in frequency domain with satisfactory dynamic performance. Simple and meticulous design algorithms for selecting the controller parameters applicable to any stable and unstable plants. Delay margin compensation technique made available for time delayed plants as well to accommodate the maximum delay that can be sustained. Exhibition and validation of simulation studies by Experimental Results of Cart-Inverted Pendulum System.